In silico analysis of the pharmacokinetic and toxicological profile of drugs in research for the treatment of COVID-19 (Research, Society and Development, 2020)
The objective of the research is to provide information on the drugs under study for the treatment of Covid-19, as well as to elucidate data on pharmacokinetic and toxicological parameters that may impact the therapy of patients affected by coronavirus, by an in silico analysis. To achieve the proposed objectives, in silico tools were used, using ACD/Chem Sketch (version 14.0) and Marvin Sketch software. The analysis of pharmacokinetic and toxicological parameters was performed through the Preadmet server, which predicts the data based on the structure/activity relationship. To complement the data collected in computational tools, a bibliographic survey was performed in the main databases on the analyzed parameters. According to the analysis of the ADME results, abiraterone and brequinar medications present the most desirable pharmacokinetic parameters. Some of the drugs observed demonstrated satisfactory responses, especially chloroquine, which met the passage parameter in the HBS, since the coronavirus has been causing manifestations in the CNS, however, this medication is related to the growth of arrhythmia deaths. On the other hand, the toxicological parameters present mostly non-mutagenic and non-ccarcinogenic drugs and, in relation to hERG, most of them are classified as medium risk. The drugs used to treat cardiopathic patients should be chosen carefully, as some of them increase cardiac risk. Ivermectin and nitazoxanide present metabolites with mutagenic potential, therefore they should be used with caution.